px*2+4x+6=0

Simple and best practice solution for px*2+4x+6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for px*2+4x+6=0 equation:


Simplifying
px * 2 + 4x + 6 = 0

Reorder the terms for easier multiplication:
2px + 4x + 6 = 0

Reorder the terms:
6 + 2px + 4x = 0

Solving
6 + 2px + 4x = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 2px + -6 + 4x = 0 + -6

Reorder the terms:
6 + -6 + 2px + 4x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 2px + 4x = 0 + -6
2px + 4x = 0 + -6

Combine like terms: 0 + -6 = -6
2px + 4x = -6

Add '-4x' to each side of the equation.
2px + 4x + -4x = -6 + -4x

Combine like terms: 4x + -4x = 0
2px + 0 = -6 + -4x
2px = -6 + -4x

Divide each side by '2x'.
p = -3x-1 + -2

Simplifying
p = -3x-1 + -2

Reorder the terms:
p = -2 + -3x-1

See similar equations:

| 14x-2(-3x+9)=4(2x-7)-1 | | -(2x+13)=2(x+4) | | 6x-12x+39=0 | | 2(3x-1)=3x+4 | | X-4=x+8 | | Y(2-3)= | | 27x+12x=0 | | -x^2-1.5x+.44=0 | | 45x+32x=4 | | (a+4)2-(a-4)(a+4)= | | -x^2-1.5x+(4/9)=0 | | 48n=48 | | -1.5x+(4/9)=-x^2 | | 4x-6x-20=0 | | 3k^5+4k^2-6k^5-5k^5= | | a+28=7a | | =(1x+2y)+(11x+11y) | | -15=9x+1-7x | | h=-16t^2+160t+80 | | 3x-17+2x=13 | | .5x-2y=4 | | 6(20x/9+15)=-150 | | 185-6x=39x+15 | | v/f | | 97-6x=12+21 | | x/2+x=400 | | -2=-1x+4 | | 1/37/27 | | 5x-6x+3=2x | | -2(2x+5)=5(x+8) | | 10=44x^2/25^2+x+6 | | x/3=5(x-2) |

Equations solver categories